The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ac902460d
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Fragrance Release from Cotton Towels by Low Thermal Mass Gas Chromatography Using a Longitudinally Modulating Cryogenic System for Headspace Sampling and Injection

Abstract: An innovative headspace sampling and injection system for gas chromatography was designed using a longitudinally modulating cryogenic system mounted around the sampling loop of a two-position loop injector. The setup was hyphenated to a fast low thermal mass gas chromatograph, allowing transient concentrations of semivolatile analytes to be monitored in real time with a time resolution of 4.5 min. The performance of the instrument, and in particular its cryotrapping efficiency, was characterized using a mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…It has been proved that the aroma perception is maintained for several days in fabrics if fabrics impregnated with capsules containing perfume and the capsules continue to emit aroma for up to five wash cycles. [11][12][13] Fragrance encapsulated in small particles (nanometer range) and narrow dispersion are preferred for use in textiles as they can provide a strong adhesive force and interact with the fibre due to their large surface area. [14] Furthermore, the smaller the capsules the greater the covering of the product and the longer the fragrance will last because it takes longer for the capsules to be ruptured by physical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that the aroma perception is maintained for several days in fabrics if fabrics impregnated with capsules containing perfume and the capsules continue to emit aroma for up to five wash cycles. [11][12][13] Fragrance encapsulated in small particles (nanometer range) and narrow dispersion are preferred for use in textiles as they can provide a strong adhesive force and interact with the fibre due to their large surface area. [14] Furthermore, the smaller the capsules the greater the covering of the product and the longer the fragrance will last because it takes longer for the capsules to be ruptured by physical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the MF microcapsules, the release of the fragrance would be based on other mechanisms such as diffusion through the polymeric microcapsule wall. Other authors have reported this kind of release due to the permeability of the shell and it is triggered by rubbing caused during the wearing of the footwear …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the widespread use of real-time monitoring technology has included spectroscopic methods [5], chromatography, and chromatography coupled with spectral detection [6][7]. At present, gas chromatography is the most commonly used real-time on-line analysis technology [8].…”
Section: Introductionmentioning
confidence: 99%